Pharmacogenomic vs. Non-Pharmacogenomic Treatment in First-Episode Depression: A Randomized Clinical Trial - Jie Tong; Jie Zhang; Na Zhu; Xiaoxue Li; Xiaochun Zhu; Yuanyuan Xu; Meiling Liu; Jie Yuan; Xirong Sun (Future Pharmacology, 2026)
Background: Due to drug efficacy, adverse reactions, and individual differences, clinicians face significant challenges in drug selection for the treatment of depression. However, the study on predicting antidepressant treatment response based on pharmacogenomics has not yet been determined. Methods: A total of 178 participants were recruited and randomly assigned to either pharmacogenomics-guided antidepressant treatment or regular antidepressant treatment. All participants completed pharmacogenomic sampling at baseline and underwent neuropsychological systemic assessments at baseline and at 4-week, 8-week, 16-week, and 32-week follow-ups. Results: Compared with the control group, the pharmacogenomics-guided group showed significant differences in the effect of DARS scores within 32 weeks (PBonferroni < 0.05), showing a significant time and group effect (p < 0.001; p = 0.007, respectively). In addition, the pharmacogenomic-guided group showed significant differences in ASEC scores within 32 weeks (PBonferroni < 0.05), showing a significant time effect, group effect, and group × time effect (p < 0.001; p = 0.018; p = 0.009, respectively). However, there was no significant difference in HAM-D17, HAM-A, PDQ-D, and PSQI between the two groups within 32 weeks (PBonferroni > 0.05). Conclusions: Pharmacogenomics-guided antidepressant prescribing effectively alleviates anhedonia and reduces adverse effects in patients with first-episode depression, but there is no significant improvement in major psychopathological symptoms. These findings carry important implications for the early application of pharmacogenomic testing in primary care settings for depression.